1989
DOI: 10.1177/37.2.2463300
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization in normal tissues of different epitopes in the multidrug transport protein P170: evidence for localization in brain capillaries and crossreactivity of one antibody with a muscle protein.

Abstract: MAb C219 showed intense localization in selected skeletal muscle fibers and all cardiac muscle fibers in rat and human tissues. ATPase cytochemistry showed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
244
0
5

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(253 citation statements)
references
References 23 publications
4
244
0
5
Order By: Relevance
“…The transporting P-gps are generally overexpressed in tumor cells, conferring resistance against cytotoxic agents and are associated with specialized normal tissue barriers (e.g., blood-brain barrier, blood-testis barrier, blood-ovarian barrier, placenta, gastrointestinal epithelium, etc.) [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transporting P-gps are generally overexpressed in tumor cells, conferring resistance against cytotoxic agents and are associated with specialized normal tissue barriers (e.g., blood-brain barrier, blood-testis barrier, blood-ovarian barrier, placenta, gastrointestinal epithelium, etc.) [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the substrates for P-gp are toxic compounds of natural or semisynthetic origin [5]. P-gp is expressed in various normal human tissues, such as small intestine, kidney, liver, and capillary endothelial cells of brain and testes [6][7][8]. Based on the tissue distribution, P-gp has been proposed to have a significant role in the protection of organisms against toxic xenobitics [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…MDR1-type P-glycoprotein has been found in the apical membrane of the intestinal epithelial cells (Mukhopadhyay et al 1988), in the biliary canalicular membrane of hepatocytes, and in the lumenal membrane of proximal tubular epithelial cells in the kidney (Thiebaut et al 1987(Thiebaut et al , 1989. High levels of MDR1 P-glycoprotein have been found in the lumenal membrane of the endothelial cells that line small blood capillaries and form the blood-brain and blood-testis barrier (Thiebaut et al 1989;Cordon-Cardo et al 1989Tsuji et al 1992).…”
Section: Mice With a Genetic Disruption (Knockout) Of The Multiple Drmentioning
confidence: 99%
“…High levels of MDR1 P-glycoprotein have been found in the lumenal membrane of the endothelial cells that line small blood capillaries and form the blood-brain and blood-testis barrier (Thiebaut et al 1989;Cordon-Cardo et al 1989Tsuji et al 1992). In addition, it has been demonstrated that P-glycoprotein found in the blood-brain barrier limits the brain accumulation of many drugs (Schinkel 1995a).…”
Section: Mice With a Genetic Disruption (Knockout) Of The Multiple Drmentioning
confidence: 99%
“…Pgp is a drug e ux pump that is present on the luminal surface of brain capillary endothelial cells [3,4]. It appears to play an important role in excluding xenobiotics, including a variety of anticancer drugs, from the CNS [5±8].…”
Section: Introductionmentioning
confidence: 99%